Chemical composition and biological activities of acetone extract from the fruit of Acronychia pedunculata - Nguyen, Ngoc An; Pham, Tan Viet; Nguyen, Thi Phuong Thuong; Nguyen, Thi Thanh Binh; Huynh, Nguyen Tuong An; Nguyen, Quoc Hung; Le, Thanh Tho; Le, Van Son; Nguyen, Hanh Thi Dieu (Journal of Phytology, 2024)
Acronychia pedunculata, a member of the Rutaceae family, has long been used in traditional medicine in South and Southeast Asia. This study provides the first comprehensive analysis of the phytochemical constituents, volatile compounds, antibacterial, and antioxidant properties of the acetone extract from A. pedunculata fruit. The results revealed that the extract contains several bioactive compounds, including phenolics, tannins, coumarins, terpenoids, steroids, and flavonoids. Additionally, 26 volatile compounds were identified, with 3-furaldehyde; 4H-pyran-4-one, 2,3-dihydro-3,5-dihydroxy-6-methyl-; and 5-hydroxymethylfurfural being the major components. The extract demonstrated antibacterial activity against three of the six tested bacterial strains: Bacillus cereus, Pseudomonas aeruginosa, and Staphylococcus aureus. It also exhibited ABTS radical-scavenging activity with an IC50 value of 223.62±4.83 μg/mL.